2001
DOI: 10.1021/jp0044429
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Determination of Titanium Lattice Defects and Solid-State Reaction Mechanism in Iron-Doped TiO2 Photocatalysts

Abstract: Iron-doped titania photocatalysts with different iron contents were prepared by using a sol−gel method in acidic media. The crystalline structures of the various phases calcined at temperatures ranging from 70 to 800 °C were studied by using the Rietveld technique in combination with XRD experiments. The average crystallite size of the phases, lattice cell parameters, phase concentrations, and titanium cationic defects in the crystalline structures of different samples were quantitatively determined. Both iron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
157
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(168 citation statements)
references
References 27 publications
7
157
1
3
Order By: Relevance
“…In addition, the sample s-0.05-620, has a very low surface area, (less than 5 m 2 /g). This sudden drop in surface area is associated primarily with the presence of rutile in this sample (25), as well as with the synthesis method. When these results are compared with those of the crystal sizes in Figure 2, a correlation between the increase in crystal size and the decrease in surface area for the effect of increasing calcination temperature is observed (31).…”
Section: Surface Areamentioning
confidence: 92%
See 2 more Smart Citations
“…In addition, the sample s-0.05-620, has a very low surface area, (less than 5 m 2 /g). This sudden drop in surface area is associated primarily with the presence of rutile in this sample (25), as well as with the synthesis method. When these results are compared with those of the crystal sizes in Figure 2, a correlation between the increase in crystal size and the decrease in surface area for the effect of increasing calcination temperature is observed (31).…”
Section: Surface Areamentioning
confidence: 92%
“…In addition, mixtures of oxides are unlikely because the amount of iron is very small. According to Wang et of 5% or more (25). Other researchers state that during the calcination process, the preadsorbed precursor (iron nitrate, for example) is decomposed, and the iron initially present at the surface diffuses into the bulk, producing a solid solution.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that doping transition metal was a useful technique for extending the absorbance of TiO 2 into the visible region [16]. For doping, various metal ions have been used, but among them, Fe 3+ is considered as a strong candidate as it has a similar radius to Ti 4+ (Fe 3+ = 78.5 pm, Ti 4+ = 74.5 pm) [17] and can easily fit into the crystal lattice of TiO 2 [16,18,19] [16,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…For doping, various metal ions have been used, but among them, Fe 3+ is considered as a strong candidate as it has a similar radius to Ti 4+ (Fe 3+ = 78.5 pm, Ti 4+ = 74.5 pm) [17] and can easily fit into the crystal lattice of TiO 2 [16,18,19] [16,18,19]. Due to easy availability as well as the above described characteristics, Fe is selected as the dopant in the present study.…”
Section: Introductionmentioning
confidence: 99%